2008
DOI: 10.1007/s11606-008-0664-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity Evidence for Medical Education Research Study Quality Instrument Scores: Quality of Submissions to JGIM’s Medical Education Special Issue

Abstract: Background Deficiencies in medical education research quality are widely acknowledged. Content, internal structure, and criterion validity evidence support the use of the Medical Education Research Study Quality Instrument (MERSQI) to measure education research quality, but predictive validity evidence has not been explored. Objective To describe the quality of manuscripts submitted to the 2008 Journal of General Internal Medicine ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
196
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 223 publications
(214 citation statements)
references
References 21 publications
7
196
1
10
Order By: Relevance
“…Our findings are consistent with the results of Reed et al, which looked at MERSQI scores for full manuscripts in MERSQI Medical Education Research Study Quality Instrument, UME undergraduate medical education, GME graduate medical education, CME continuing medical education MERSQI Medical Education Research Study Quality Instrument, UME undergraduate medical education, GME graduate medical education, CME continuing medical education both original research and education innovations. 14 In this study, the average MERSQI score was 10.3 (SD 2.2) for original articles, compared to 8.3 (SD 2.7) for educational innovations, which is comparable to the difference of 1.57 in our study. 14 The current study also demonstrated a lower acceptance rate of 23 % for IME abstracts compared to 42 % for scientific medical education abstracts.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings are consistent with the results of Reed et al, which looked at MERSQI scores for full manuscripts in MERSQI Medical Education Research Study Quality Instrument, UME undergraduate medical education, GME graduate medical education, CME continuing medical education MERSQI Medical Education Research Study Quality Instrument, UME undergraduate medical education, GME graduate medical education, CME continuing medical education both original research and education innovations. 14 In this study, the average MERSQI score was 10.3 (SD 2.2) for original articles, compared to 8.3 (SD 2.7) for educational innovations, which is comparable to the difference of 1.57 in our study. 14 The current study also demonstrated a lower acceptance rate of 23 % for IME abstracts compared to 42 % for scientific medical education abstracts.…”
Section: Discussionsupporting
confidence: 83%
“…14 In this study, the average MERSQI score was 10.3 (SD 2.2) for original articles, compared to 8.3 (SD 2.7) for educational innovations, which is comparable to the difference of 1.57 in our study. 14 The current study also demonstrated a lower acceptance rate of 23 % for IME abstracts compared to 42 % for scientific medical education abstracts. Furthermore, Reed et al found that educational innovations scored significantly lower in the same domains that we identified (sampling, validity, and data analysis).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations